IMPLEMENTASI METODE TOPSIS UNTUK SISTEM PEMILIHAN PROGRAM STUDI PADA PERGURUAN TINGGI DI SMA NEGERI 2 KUPANG - Yoshua Patriot Thundericco; Nelcy Rumlaklak; Tiwuk Widiastuti (Universitas Nusa Cendana, 2019)
Proceeding study to the college is something that most of twelfth grade students wants. However, they are still confused in chossing study program because due to not knowing their own aptitude and interest. To solve that problem, some factors are used, which are cognitive factor, by doing psychological test, and affective factor, by observing the tendency of their subjects in high school. Therefore, this research will design and develop a decision support system for study program determination in college using TOPSIS method. This method is chosen due to its capability in choosing best alternative out of multicriteria alternatives. Criterias that are used for this study includes Academic Criteria (Language, Logic, Science, Practice, and Social) and Aptitude Criteria (Intelligence, Space Reasoning, Mechanical, Abstract Reasoning, Verbal Reasoning, Numeric, Language Usage). The test is conducted through confusion matrix method. From 60 test-data, 13 data have difference between the system-result and real-result, thus the system is 78.33% accurate.